If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(4x + 3) + 4(-6x + 1) = 43 Reorder the terms: -3(3 + 4x) + 4(-6x + 1) = 43 (3 * -3 + 4x * -3) + 4(-6x + 1) = 43 (-9 + -12x) + 4(-6x + 1) = 43 Reorder the terms: -9 + -12x + 4(1 + -6x) = 43 -9 + -12x + (1 * 4 + -6x * 4) = 43 -9 + -12x + (4 + -24x) = 43 Reorder the terms: -9 + 4 + -12x + -24x = 43 Combine like terms: -9 + 4 = -5 -5 + -12x + -24x = 43 Combine like terms: -12x + -24x = -36x -5 + -36x = 43 Solving -5 + -36x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -36x = 43 + 5 Combine like terms: -5 + 5 = 0 0 + -36x = 43 + 5 -36x = 43 + 5 Combine like terms: 43 + 5 = 48 -36x = 48 Divide each side by '-36'. x = -1.333333333 Simplifying x = -1.333333333
| (5/4)^-1 | | x^2+7x-13=17 | | n=9/10 | | x^2+10x+y^2+14y=-49 | | 4.9m+(-3.2m)-13=2.63 | | 5/4y^2+y+25=0 | | 120-15x=x | | 2(6x+5)=58 | | 5x=8x-y | | 2/3n+3/8n=15/16 | | 2x+3y=15y | | -1/7(8+5x)=-53/7 | | -3*x^2-2*x+5=0 | | 25+m/2=30 | | 5/4y^2-25=0 | | 2(5-4x)=-62 | | -15/-3=-5 | | 7(-7-7x)=-245 | | x^2-8*x+3=0 | | -X^3+63X+162=0 | | 68/21k=131/3 | | 9j+4=13j+6 | | (-1/2y)^2=0 | | 2p+10=36 | | 0=x^2+5*x+1 | | (-1/2y)^2 | | y=x^2+5*x+1 | | 4m+12=48 | | -16t^2+48t+8=0 | | (-1/2y)^2+y^2=25 | | 8x^2+4x+16=0 | | f(x)=x^2+5*x+1 |